VD_FINDINFO Jug / 2023 / 259 vom 26. Oktober 2020 - VD Tribunal cantonal (2020)
DEMANDE ADRESSÉE À L'AUTORITÉ, PROCÉDURE ÉCRITE, RÉVISIONDÉCISION | 410 al. 1 let. a CPP (CH), 412 al. 1 CPP (CH), 412 al. 2 CPP (CH)